Efektifitas Hara Dalam Pemupukan Pada Tanaman Padi (Oryza Sativa L.): Studi Kasus Dosis Pemberian Pupuk NPK Phonska - Agus Fahmi (Corolla: Jurnal Sains Pertanian, 2015)
This study aims to find the effectiveness of fertilizer nutrients in rice plants with NPK Phonska .. By using a factorial randomized block design (RAK) with 2 (two) factor of three (3) replicates. Factor I = Spacing (A) consisting of (2) two levels, namely: J1 = spacing of 20 cm X 20 cm, J2 = spacing of 25 cm X 25 cm. Factor II = dosage of NPK fertilizer Phonska (D) consisting of three (3) levels, namely: D1 = dosage of 250 kg / ha of NPK Phonska D2 = dosage of 300 kg / ha NPK Phonska, D3 = dosage of 350 kg / ha NPK Phonska. Observations were made by taking samples on grids treatment each - each as much as 5 sample. Adapaun parameters are observed: 1) High rods, from ground level up to the last segment 2) Number of tillers 3) the number of panicles 4) Weight of 100 seeds. Effectiveness obtained fertilizer nutrients in rice plants with NPK Phonska specified parameters: growth, plant height, number of tillers, heavy stover, and production parameters occurs at an average age of 35 to 55 day period to grow rice with a certain dose.